Comparison of Neurocognitive Performance in Contact and Noncontact Nonconcussed High School Athletes Across a Two-Year Interval. Issue 1 (17th February 2017) - Brett, Benjamin L.; Solomon, Gary S.
ABSTRACT: Investigating short-term effects of subconcussive impacts on neurocognitive functioning, we employed a repeated measures multivariate model and regression-based measure to examine neurocognitive changes in 771 contact and noncontact high school athletes over a two-year period. Results reveal significant changes in Visual Motor Speed for both groups over a two-year period, with small effect sizes. According to regression-based measures, differences in contact sport athletes' expected Time 2 performances were significant for Visual Motor Speed, also with minimal effects. Results do not conclusively implicate subconcussive hits as the offending factor in differences observed, with gender and sport-type possibly contributing to the small effects.